Blocking Formation of the Stable HIV Reservoir: A New Perspective for HIV-1 Cure - Goonetilleke, Nilu; Clutton, Genevieve; Swanstrom, Ron; Joseph, Sarah B. (Frontiers in Immunology, 2019)
Recent studies demonstrate that the stable HIV-1 reservoir in resting CD4+ T cells is mostly formed from viruses circulating when combination antiretroviral therapy (ART) is initiated. Here we explore the immunological basis for these observations. Untreated HIV-1 infection is characterized by a progressive depletion of memory CD4+ T cells which mostly express CD127, the α chain of the IL-7 receptor (IL-7R). Depletion results from both direct infection and bystander loss of memory CD4+ T cells in part attributed to dysregulated IL-7/IL-7R signaling. While IL-7/IL7R signaling is not essential for the generation of effector CD4+ T cells from naïve cells, it is essential for the further transition of effectors to memory CD4+ T cells and their subsequent homeostatic maintenance. HIV-1 infection therefore limits the transition of CD4+ T cells from an effector to long-lived memory state. With the onset of ART, virus load (VL) levels rapidly decrease and the frequency of CD127+ CD4+ memory T cells increases, indicating restoration of effector to memory transition in CD4+ T cells. Collectively these data suggest that following ART initiation, HIV-1 infected effector CD4+ T cells transition to long-lived, CD127+ CD4+ T cells forming the majority of the stable HIV-1 reservoir. We propose that combining ART initiation with inhibition of IL-7/IL-7R signaling to block CD4+ T cell memory formation will limit the generation of long-lived HIV-infected CD4+ T cells and reduce the overall size of the stable HIV-1 reservoir.